Determinação da estrutura de diferentes alcoóis terpênicos: um estudo teórico e experimental - Marana, Naiara Letícia [UNESP]; Ducati, Lucas Colucci; Silva Filho, Luiz Carlos da [UNESP] (My University, 2013)
Terpene compounds is a major class of natural products found in nature, although having a relatively simple structure, their 1H-NMR spectra and 13C are complex and have many overlapping signals. The present study aimed to conduct a theoretical and experimental study in order to determine the structure of different chiral alcohols through the use of theoretical calculations of NMR shielding tensors (δ) and their comparison with the experimental chemical shifts. The results show that the level of theory adopted in our studies to describe the structure of the alcohol was adequate, with a good theoretical and experimental correlation assists in determining what structure.
Keywords: Terpenic alcohol; Correlation study; NMR; Ab-initio calculations